Tri Hita Karana: A contemporary sculpture creation - Pande Putu Ogy Mega Sanjaya; I Wayan Adnyana; I Ketut Muka (Institut Seni Indonesia Denpasar, 2022)
Tri Hita Karana in Hinduism is the understanding of three main things that cause prosperity for human life which consist of Parhyangan, Pawongan, and Palemahan. The phenomenon stimulates creator to create a sculpture that aimed to provide an understanding related to Tri Hita Karana. The method applied in this creation uses five stages, namely the search for ideas, the search for materials, experiments, the embodiment of the work, and the presentation of the work. In this creation of three-dimensional works of art in the form of sculptures, the creator tries to express Tri Hita Karana issues with the concept of recycle, a process to turn used materials into new materials with the aim of preventing waste that can actually be turned into useful goods. The form of the work will be in the form of contemporary sculpture by displaying unique and authentic new forms. Keywords: Tri Hita Karana, recycle, contemporary sculpture.